Semiotics of interface and users interaction - Paulino, Rita de Cássia Romeiro; Perassi, Richard; Fialho, Francisco Antônio P. (InfoDesign, 2011)
The object of study presented in this paper proposes a semiotic analysis of n e-mail viewer, as an interface differentiated from existing models for e-mail reading, selection and organization. The peircean semiotic theory assists in the interpretation and understanding of the ways in which users interact with the web environment and allows understanding of the processes of significance set by users while interacting with a web interface. [ Download ]